The human brain : an introduction to the human nervous system (Přít.) - Hall, Marion; Robinson, David (Springer, 1998)
Both students and non-scientists will find this CD-ROM an enjoyable introduction to the human brain. The seven sections cover the structure and function of the brain, spinal cord, hearing, vision, and speech. The voice-over gives guidance in the pronunciation of Latin names of various brain substructures. The CD-ROM includes photos, video clips and animations, and a rotatable model of the brain which allows various substructures to be highlighted. The self-testing function allows a continual assessment of understanding, and students can keep their own record of images using the built-in photo album. The textbook \"Neurobiology\" by D. Robinson which can be used in conjunction with the CD-ROM can be purchased separately (ISBN3-540-63546-7) or together with the CD-ROM (ISBN3-540-63778-8).
Keywords: Nervous System; mozek; nervový systém; Brain; neurologie